Corporate Governance and Quality of Employees Performance: A Conceptual Analysis - Saheb Shaker, Ameer; Badr Ezghayer, Hayder; Abdulzahra Adam, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
This paper aims to achieve a general goal is to explore the concept of governance in economic units and its role in achieving economic and social development. It also aims to show the positive effects of applying the rules of governance in economic units and knowing the relationship of the concept of governance to performance in economic units. The research also seeks to discover how to develop the services provided by the units, enhance their quality, and improve and develop the performance of employees of economic units. The results show the necessity of enhancing the level of knowledge of all employees in economic units with concepts and standards of governance because of their role in improving job performance. The results also show the importance of establishing the rule of law as it works to control the work of economic units and its reflection on performance through periodic monitoring of the employees ’work in those units. This requires beginning to implement the actual standards of governance in economic units to reduce administrative and financial corruption and enhance the level of employee performance.